2023
DOI: 10.1128/spectrum.05211-22
|View full text |Cite
|
Sign up to set email alerts
|

FAM46C Is an Interferon-Stimulated Gene That Inhibits Lentiviral Particle Production by Modulating Autophagy

Abstract: FAM46C role has been thoroughly investigated in MM, but studies characterizing its role outside of the tumoral environment are still lacking. Despite the success of antiretroviral therapy in suppressing HIV load to undetectable levels, there is currently no HIV cure, and treatment is lifelong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Early studies correlated FAM46C expression with IFN responses [1], but only recently has our lab actually demonstrated that FAM46C expression is induced upon type I and type II IFN administration. Specifically, we showed that this is true for both IFN-α and IFN-γ in macrophages, CD4 + T and dendritic cells [4]. However, unlike common ISGs, whose expression increases up to 1000-fold upon IFN administration, we found that FAM46C is upregulated only 2-to 4-fold, based on the stimuli and cell type analysed, suggesting it to be an overall weak ISG.…”
Section: Ifn-α and -γmentioning
confidence: 72%
See 3 more Smart Citations
“…Early studies correlated FAM46C expression with IFN responses [1], but only recently has our lab actually demonstrated that FAM46C expression is induced upon type I and type II IFN administration. Specifically, we showed that this is true for both IFN-α and IFN-γ in macrophages, CD4 + T and dendritic cells [4]. However, unlike common ISGs, whose expression increases up to 1000-fold upon IFN administration, we found that FAM46C is upregulated only 2-to 4-fold, based on the stimuli and cell type analysed, suggesting it to be an overall weak ISG.…”
Section: Ifn-α and -γmentioning
confidence: 72%
“…Different studies demonstrated that this does not seem to be the case [10,13,65], and a mechanism other than poly(A) adenylation of PTEN was proposed, namely PTEN protein stabilization through inhibition of its poly-ubiquitination [10], underlining a strict connection between FAM46C and the proteasomal machinery. FAM46 proteins were indeed already shown to be involved in protein stability, as FAM46C antiviral activity was shown to depend on autophagic dampening, an event which in turn was proposed to render viral proteins more susceptible to proteasomal degradation [4], and FAM46B was demonstrated to favour ubiquitination of β-catenin in BC cells [36]. How this effect enters the already intricate picture of FAM46C functions is hard to define and will for sure be the focus of future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations